PENGARUH LEVERAGE DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Camila, Melda Nahda; Karnadi, Karnadi; Wiryaningtyas, Dwi Perwitasari (Fakultas Ekonomi dan Bisnis, 2023)
The purpose of this study is to determine the effect of leverage and capital structure on company value with earnings management as an intervening variable in food and beverage companies listed on the IDX in 2019-2021. The population in this study was all companies listed on the IDX, 30 food and beverage companies. The sampling technique in this study used purposive sampling so that 12 samples of data analysis were obtained. Data analysis and hypothesis testing in this study used the Smart PLS 3.0 application. The results of this study indicate that leverage and capital structure have no significant effect on earnings management. Leverage has a significant negative effect on company value, while capital structure and earnings management have no significant effect on company value. Leverage and capital structure have no significant effect on company value through earnings management.